Apolipoprotein E dysfunction in Alzheimer’s disease: a study on miRNA regulation, glial markers, and amyloid pathology - Wijesinghe, Printha; Li, Hao Ran; Ai, Zhengyuan; Campbell, Matthew; Chen, Si Xuan; Xi, Jeanne; Pham, Wellington; Matsubara, Joanne A. (Frontiers in Aging Neuroscience, 2024)
IntroductionApolipoprotein E (ApoE) plays a crucial role in lipid homeostasis, predominantly expressed in astrocytes and to a lesser extent in microglia within the central nervous system (CNS). While the APOE4 allele is the strongest genetic risk factor for late-onset Alzheimer’s disease (AD), its precise role in AD pathogenesis remains elusive. Apoe-knockout (Apoe-ko) mice, mice expressing human APOE4, and human APOE4 carriers exhibit similar deficits in lipid metabolism, cognitive and behavioral functions, and neurodegeneration. The retina, as part of the CNS, has been studied to investigate the underlying mechanisms of AD, including neuroinflammation, amyloid aggregation, and neurodegeneration. This study explores ApoE’s role in AD by analyzing brain and eye samples from Apoe-ko mice, focusing on identifying potential retinal biomarkers associated with ApoE dysfunction.MethodsWe compared female Apoe-ko mice on a regular diet to age-matched C57BL/6J controls at 3 and 9 months. Our investigations included microRNAs (miRNAs), their target messenger RNAs (mRNAs), and selected protein markers, including astroglial (Gfap), microglial/macrophage (Iba1 and Trem2) markers, and amyloid precursor protein (APP)/amyloid-β (Aβ) peptides implicated in AD pathogenesis. We also examined female Apoe-ko mice on a high-fat diet versus a regular diet at 9 months for differential miRNA and mRNA expressions.ResultsOur findings demonstrated that miRNA levels were generally lower in 3-month-old Apoe-ko mice but increased in 9-month-old mice across five distinct brain regions, as well as in eye tissue and tear fluid. A high-fat diet further enhanced miRNA dysregulation in brain and eye tissues, but not in tear fluid. Target mRNAs were generally higher in the neocortex-hippocampus and eye tissue of 3-month-old Apoe-ko mice but decreased with age, except for glial cell mRNAs like Gfap and Aif1. Protein analysis revealed elevated Gfap expression, and increased APP/Aβ peptide accumulation in the neocortex-hippocampus, including brain endothelial cells at the meninges, as well as in the retina of 9-month-old Apoe-ko mice. These findings highlight ApoE’s pivotal role in AD, demonstrating its impact on inflammatory and amyloidogenic/angiogenic miRNA expression, glial homeostasis, and APP/Aβ peptide clearance. The observed upregulation of proinflammatory miR-146a and anti-amyloidogenic/angiogenic miR-15a in 9-month-old Apoe-ko mice suggests their potential as tear-based biomarkers for ApoE dysfunction.